1999
DOI: 10.1257/aer.89.2.381
|View full text |Cite
|
Sign up to set email alerts
|

Financial Decision-Making: Are Women Really More Risk Averse?

Abstract: A widespread view concerning financial decision-making is that women are more riskaverse than men. A consequence of this stereotype is statistical discrimination which diminishes the success of women in financial and labor markets. The perception that female managers are less risk-prone than men has been put forward as a major cause of ''glass ceilings'' in corporate promotion ladders (Johnnie E. V. Johnson and Philip L. Powell, 1994). Women are less trusted than men to make the risky decisions that may be nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
345
5
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 619 publications
(396 citation statements)
references
References 8 publications
23
345
5
13
Order By: Relevance
“…Among the three largely exogenous variables, gender has a consistently negative and highly significant sign. This is new for our data and is not to be expected in the context of experiments from advanced economies, where women are more risk averse than men in abstract experiments but not so in a contextual environment (Schubert et al, 1999). Eckel and Grossman (2008) summarize the evidence that a greater female risk aversion "is less conclusive" in a contextual environment.…”
Section: Results On a Hypothetical Investment Lotterymentioning
confidence: 61%
“…Among the three largely exogenous variables, gender has a consistently negative and highly significant sign. This is new for our data and is not to be expected in the context of experiments from advanced economies, where women are more risk averse than men in abstract experiments but not so in a contextual environment (Schubert et al, 1999). Eckel and Grossman (2008) summarize the evidence that a greater female risk aversion "is less conclusive" in a contextual environment.…”
Section: Results On a Hypothetical Investment Lotterymentioning
confidence: 61%
“…Nonetheless, when comparing the ratio of risky assets to net worth for the same age categories, there was no significant difference in this ratio for men and women younger than forty years but women over forty years had a lower than men in the same age category. Add to that, Schubert, Brown, Gysler and Brachinger, (1999) showed that the differences in the financial risk tolerance of males and females depending on the financial decision frame. Moreover, Strydom and Metherell (2012) revised findings of previous studies that males were more risk loving than females and concluded that the differences in risk attitudes between males and females may due to that opportunity sets rather than stereotypic risk attitudes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Harbaugh et al (2002) and Holt and Laury (2002) conduct abstract experiments with real rewards, and find no significant sex effects on elicited risk aversion when stakes are non-trivial. Schubert et al (1999) conduct abstract and non-abstract experiments with real rewards and conclude that women do appear to be more risk averse than men in abstract tasks in the gain frame, but that this effect disappears with context. Unfortunately, they employed the Becker-DeGroot-Marschak procedure for eliciting certaintyequivalents, which is known to have poor incentive properties for experimental subjects.…”
Section: Page 19 Of 35mentioning
confidence: 99%